Konsep Tauhid dalam Perspektif Syekh Bin Baz dan Implementasinya dalam Dakwah dan Pendidikan di Era Global: The Concept of Tawhid from Sheikh Bin Baz's Perspective and Its Implementation in Da'wah and Education in the Global Era - Samsuddin, Samsuddin; Rahendra Maya; Agusman, Agusman (Litera Academica Publishing, 2024)
Tawhid is the core of Islamic teachings and is the fundamental basis for all aspects of a Muslim's life. Understanding of tawhid is not only limited to theory, but must be realized in daily practice through worship, morals, and social interaction. In the history of Islam, scholars played an important role in spreading the understanding of tawhid, continuing the mission of the Prophets. One of the scholars who contributed greatly to this was Sheikh Abdul Aziz bin Abdullah bin Baz, whose thoughts on tawhid became the main reference in Islamic preaching and education. This study aims to describe and analyze the concept of tawhid according to the perspective of Sheikh Bin Baz, as well as its implementation and relevance in preaching and education in the global era. This study uses a qualitative approach with a literature study method, analyzing Bin Baz's main works and related literature. The results of the study show that Sheikh Bin Baz emphasized the urgency and centrality of tawhid in Islamic teachings, with a focus on three aspects: tauhid rububiyyah, uluhiyyah, and asma' wasifat. This article also discusses the findings on the importance of integrating monotheism in education to ensure a clear understanding of faith among Muslims, especially in facing the challenges of modern ideologies such as secularism, liberalism, and pluralism. The implications of these findings indicate that monotheism is an effort to protect Islamic beliefs and plays an important role in shaping educational curricula, thus producing devout Muslims who are able to face contemporary challenges. This study contributes to the discourse on the relevance of monotheism in modern da'wah and education, providing insights for educators and preachers in upholding the teachings of monotheism in Islam.